STRATEGI PEMBELAJARAN SENI TARI BERBASIS PRAKTIK SEBAGAI RESPONS TERHADAP TANTANGAN PENDIDIKAN SENI MASA KINI : STUDI LITERATUR - Miranda Jamil, Alhani; Astuti, Fuji; Nerosti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine practice-based dance learning strategies as a response to contemporary challenges in arts education. As an integral component of arts education, dance learning requires direct engagement through bodily experience, exploration, and reflective processes. However, current educational practices tend to prioritize theoretical approaches, which often limit students’ active participation in learning. This research employed a qualitative descriptive approach using a qualitative literature review method. Data were collected from national and international scholarly sources, including peer-reviewed journal articles, academic books, and educational policy documents published between 2020 and 2025. The data were analyzed thematically to identify key challenges, conceptual patterns, and pedagogical strategies related to practice-based dance learning. The findings indicate that practice-based learning strategies play a crucial role in addressing contemporary challenges in arts education by enhancing student engagement, creativity, and aesthetic experience. Furthermore, such strategies contribute to strengthening cultural awareness and contextualized learning. The study concludes that practice-based dance learning offers significant theoretical and practical contributions to the development of contemporary arts education and provides a relevant pedagogical framework for educators in designing meaningful and experience-oriented dance learning processes.